Ecotoxicological evaluation the effects of the safe concentration of wastewater containing phenol on aquatic ecosystems - Bezverbna, Olena; Załęska-Radziwiłł, Monika (Journal of Environmental Engineering and Landscape Management, 2018)
The aim of this study was to identify the toxicity, determine and verify safe concentration of effluents containing phenol to the aquatic ecosystems on the basis of single- and multispecies ecotoxicological bioassays. Synthetic wastewater imitating municipal sewage showed acute toxicity in relation to all bioindicators and belonged to the third toxicity class. The most sensible organism was Danio rerio, the most resistance organism was Desmodesmus quadricauda. Chronic safe concentration of wastewater containing phenol was 0.63% which corresponded to 0.63 mg/l of phenol. Appointed safe concentration and the one ten times higher than safe were verified in microcosm study, which confirmed that safe concentration did not cause toxic effects. Maximum permissible concentration of phenol in water bodies does not exceed determined concentration in different countries. Proposed research model can be used to determine and verify safe concentrations for aquatic ecosystems of many types of sewage from various industries.